THE ROLE OF RENEWABLE ENERGY IN REDUCING CO2 EMISSIONS IN UZBEKISTAN - Shoh-Jakhon Khamdamov; Anvar Usmanov (Journal of Artificial Intelligence and Digital Economy, 2024)
The transition to renewable energy is a key strategy for reducing CO2 emissions and promoting green growth in Uzbekistan. This paper explores the role of renewable energy sources, including solar, wind, and hydropower, in reducing carbon emissions within the country’s energy mix. Uzbekistan’s current energy system remains heavily reliant on fossil fuels, particularly natural gas, which is a significant contributor to CO2 emissions. By analyzing the potential of renewable energy and government initiatives to support its growth, this study assesses the progress made and identifies challenges that hinder the transition. The findings suggest that increasing the share of renewable energy will play a vital role in reducing emissions and promoting sustainable development in Uzbekistan